2013
DOI: 10.1080/00224545.2013.806292
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Source of Autonomy Support in Relation to Workers' Motivation and Self-Efficacy

Abstract: The purpose was to investigate the relationship between autonomy support by managers and co-workers and employees' work motivation and self-efficacy in two studies. In Study 1, a sample of 343 Swedish workers completed surveys, and in Study 2, we followed up with a subsample of 98 workers one year later. As in previous studies, managers support of autonomy was significantly positively related to workers' outcomes. However, the results of Study 1 also showed that co-worker autonomy support was related to these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
3
46
1
1
Order By: Relevance
“…That is, the concept describes the immediate interpersonal climate in the work environment created by their supervisors rather than the job characteristics themselves (Baard et al, 2004). Moreover, it is important to mention that recent studies of need support have highlighted the importance of need support not only from managers, but also from co-workers (e.g., Jungert, Koestner, Houlfort & Schattke, 2013;Moreau & Mageau, 2012).…”
Section: Compensation and Motivation From The Sdt Perspectivementioning
confidence: 99%
“…That is, the concept describes the immediate interpersonal climate in the work environment created by their supervisors rather than the job characteristics themselves (Baard et al, 2004). Moreover, it is important to mention that recent studies of need support have highlighted the importance of need support not only from managers, but also from co-workers (e.g., Jungert, Koestner, Houlfort & Schattke, 2013;Moreau & Mageau, 2012).…”
Section: Compensation and Motivation From The Sdt Perspectivementioning
confidence: 99%
“…Building on this, the relation between work motivation and attitude open to innovation was also established (Janz et al, 1997). It was also proved that autonomy is strengthening work motivation and self-efficacy in employees (Jungert et al, 2013). Employees attach great importance to the autonomy and are internally tied to it, and their respect for independence is reflected in internal work motivation (Fowler, 2015;Steinmann and Schreyogg, 2001).…”
Section: Motivation Of Kw and Their Job Performancementioning
confidence: 94%
“…However, innovativeness and cognitive tendencies in an employee's profile have an impact on innovation and efficiency (Lewis, Agarwal, and Sambamurthy, 2003). On the basis of the above, it can be concluded that the most important characteristics of KW include: ethics (Chong et al, 2017;Evans, 2005;Griffin, 2017;Murgia et al, 2016;Steinmann and Schreyogg, 2001;Tidd, and Bessant, 2013), autonomy (Janz, Colquitt, and Noe,1997;Jungert, Koestner, Houlfort, and Schattke, 2013), cooperation (Davenport, 2007, Jashapara, 2014Tidd, and Bessant, 2013), professionalism (Frick, 2010;Owen, 2013;Tidd, and Bessant, 2013), intellectualism (Hwang, Kettinger, and Yi, 2015), innovativeness (Fischer, Malycha, and Schafmann, 2019;Tidd, and Bessant, 2013), and reputation (Bhatnagar, Gupta, Alonge, and George, 2017;Frick, 2010;Hwang et al, 2015), as shown in Figure 1. At the same time, it is important to define the concept of the level of absorption of the KW's characteristics.…”
Section: Literature Review and Hypotheses Development 1knowledge Wormentioning
confidence: 99%
See 1 more Smart Citation
“…From an SDT perspective, autonomy support thus also fosters intrinsic motivation (Ryan & Deci, ). Many studies have shown that this holds true in organizational contexts (see for example, Gagné, Deci, & Ryan, ; Gillet, Gagné, Sauvagère, & Fouquereau, ; Jungert, Koestner, Houlfort, & Schattke, ), while motivation suffers when workers experience psychological harassment or greater pressure on the job (Fernet, Austin, & Vallerand, ; Trépanier, Fernet, & Austin, ). In addition, intervention studies have shown that support from training managers (Hardré & Reeve, ) as well as co‐workers (Jungert, Van den Broeck, Osterman, & Schreurs, ) results in employees with higher levels of motivation.…”
Section: Core Concepts Theory and Prior Researchmentioning
confidence: 99%